Monsters In The Woods : Backpacking With Children - Hauserman, Tim, 1958- (Book collections on Project MUSE., 2007)
"In this book, parents will find everything necessary to know about how to prepare, what to bring, who carries what, how far to walk, what to do in camp, safety precautions, dealing with mishaps, and proper trail and campground etiquette"--Page 4 of cover